Pengembangan Model Latihan Menggiring Bola (Dribbling) Untuk Pemain Sepak Bola Usia 10-12 Tahun - Ega Azhar Rahmadika; Imam Hariadi (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aims to develop a dribbling training model at the Mahesa Dharma Kediri Football School for ages 10-12 years. This study uses a procedural development model. The type of research conducted in this study is developmental research, according to Borg and Gall. The procedure in this study has 7 stages. The product trial design consists of expert evaluation, small group trials, and large group trials. The trial subjects in this development involved 2 football experts and 1 media expert. The small group trial subjects used 5 football players at SSB Mahesa Dharma Kediri, aged 10-12 years. The large group subjects used 15 players at SSB Mahesa Dharma Kediri, aged 10-12 years. The types of data in this study are quantitative and qualitative data. The instruments used were questionnaires and interviews. This study has been validated by several experts. The results of the validation recapitulation from media experts gave a percentage of 75%, from football coaching experts gave 88%, and for football practitioner experts gave 75%. During the small group experiment involving 5 (five) SSB Mahesa Dharma Kediri soccer players aged 10-12 years, the results reached 93%, while in the large group involving 15 (fifteen) SSB Mahesa Dharma Kediri soccer players aged 10-12 years, the results reached 91%. Through small and large group experiments and validation by each expert, the dribbling training model development module that is being developed is considered very valid and valid enough to be used as a reference for learning varied and interesting dribbling training in the field of soccer, especially for ages 10-12 years.